Feeling sad makes us feel older: effects of a sad-mood induction on subjective age - Dutt, Anne J.; Wahl, Hans-Werner (Psychology and aging, 2017)
A mood-induction paradigm was implemented in a sample of 144 adults covering midlife and old age (40-80 years) to investigate associations between mood and subjective age. Sad or neutral mood was induced by texts and music pieces. Subjective age was operationalized as felt age relative to chronological age. Participants receiving the sad-mood induction reported changes toward older felt ages from pre- to postinduction. Participants receiving the neutral-mood induction reported comparable levels of subjective age at pre- and postinduction. Effects were comparable across middle- and older aged participants. Results suggest that sad affective states might dampen subjective age.
Gesehen am 19.02.2018